Farmer services: Customized information - Madan, Hemant (Technical Centre for Agricultural and Rural Cooperation, 2010)
Nokia Life Tools delivers customized information to farmers in India and Indonesia based on their location, language and crops. The company hopes to expand the service to Africa in 2010.